The Desire for Enrichment as a Cause of Corruption of the Republic - F. V. Arkhipov (Управленческое консультирование)
This study is devoted to the problem of material enrichment in the framework of Republican political theory. The aim of the work is to determine how the private desire for wealth correlates with the republican public virtues and affects the corruptio of the republic. The fact is that the desire for enrichment is the realization of a private self-interest. At the same time, the key republican virtue for the classical period — virtu — also assumes the presence of a private interest. In this regard, the author provides a theoretical justification for the permissibility of the desire for enrichment within the framework of republicanism.The research methods are comparative, historical methods, as well as the methodology of the Cambridge school. Within the framework of the analysis of the texts of the Republican tradition, the author comes to the following results.The corruptio of the republic takes place in cases where citizens are willing to compromise with the centralized political power of the state, giving up republican freedom for the sake of security and wealth. The most striking manifestation of this compromise is the transfer to the state of the function of distributing material goods in society. Wealth itself, in accordance with the classic Republican critique of statism, becomes dangerous when it replaces virtue, or becomes the price for which a person is willing to sell his freedom.At the same time, the most dangerous form of such a deal can be called a compromise, in which republican institutions continue to function formally, but political participation in society is replaced by police state control. Corruption of morals, therefore, occurs when people are willing to give up personal freedom for the sake of material well-being and convenience. However, at the same time, there is an amazing ideological substitution, according to which the political sphere begins to be called the state apparatus, which as such suppresses politics. This is the moment at which the corruptio of the republic takes place.As a result of the study, the author concludes that an effective compromise between a deviation from republican principles and private welfare is impossible. However, the desire to enrich itself can even be useful for the republic.